Willingness to take risk and entrepreneurial intention of university students: An empirical study comparing private and state universities - YURTKORU, EMİNE SERRA (ELSEVIER SCIENCE BV, 2014)
Besides its benefits for many organizations, entrepreneurship is regarded as an important phenomenon for many studies. As a result of these studies, it is argued that entrepreneurial personality factors are insufficient to have reliable and generalizable outcomes, thus attention is reverted to intentional processes. Also risk taking willingness is believed to be distinguishing factor for entrepreneurial features. In line with literature the purpose of this study is to measure the effect of willingness to take risk on entrepreneurial intentions and compare state and private university students. 207 state and 214 private university students are analyzed and results revealed some differences between two groups and partial effect of willingness to take risk on entrepreneurial intension (C) 2014 The Authors. Published by Elsevier Ltd.
Keywords: Entrepreneurial intension; Willingness to take risk; State University; Private University